The relation of radiological tumor volume response to histological response and outcome in patients with localized Ewing Sarcoma. (21st February 2019) - Haveman, Lianne M.; Ranft, Andreas; vd Berg, Henk; Smets, Anne; Kruseova, Jarmila; Ladenstein, Ruth; Brichard, Benedicte; Paulussen, Michael; Kuehne, Thomas; Juergens, Heribert; Klco‐Brosius, Stephanie; Dirksen, Uta; et al.
Abstract: Background: Magnetic resonance imaging (MRI) is the modality of choice for local staging and response evaluation of Ewing sarcoma (EwS). Aim of this study was to determine the relevance of tumor volume response (TVR) in relation to histological response (HisRes) and survival, in order to evaluate if early modification of chemotherapy might be indicated in patients with inadequate TVR. Methods: Three dimensional (3D)‐tumor volume data at diagnosis, during early induction phase (1‐3 courses of chemotherapy; n = 195) and/or late induction phase (4‐6 courses; n = 175) from 241 localized patients were retrospectively analyzed. A distinction was made between adequate response (reduction ≥67%) and inadequate response (reduction <67% or progression). Correlations between TVR, HisRes, event free survival (EFS), and overall survival (OS) were analyzed using chi‐square tests, log‐rank tests, and the Cox‐regression model. Results: Early adequate TVR, noted in 41% of patients, did not correlate with EFS ( P = 0.92) or OS ( P = 0.38). During late induction phase 62% of patients showed an adequate TVR. EFS for patients with late adequate TVR was better (78%) than for those with inadequate late TVR (61%) ( P = 0.01); OS was 80% and 69% ( P = 0.26), respectively. No correlation was found between TVR and HisRes. Multivariate analysis showed that poor HisRes, pelvic location and late inadequate TVR were associated with poor outcome. Conclusions: Early inadequate TVR does not predict adverse outcome; therefore, changing the treatment to second line chemotherapy is not indicated in case of inadequate early TVR. Late adequate TVR and good HisRes correlate with better EFS; patients with late inadequate TVR might benefit from augmented therapy. Abstract : Early adequate tumor volume response (TVR) does not predict outcome, so modification of chemotherapy in case of an inadequate early TVR may not be justifiable. However, late adequate TVR and poor histological response were independent predictors of adverse outcome; therefore, patients with late‐phase inadequate TVR might benefit from augmented treatment.